Metacognitive Monitoring of Text Comprehension: An Investigation on Postdictive Judgments in Typically Developing Children and Children With Reading Comprehension Difficulties - Mirandola, Chiara; Ciriello, Alfonso; Gigli, Martina; Cornoldi, Cesare (Frontiers in Psychology, 2018)
The ability to assess and monitor one’s own understanding of a written text is fundamental for learning and academic achievement. In the current paper, postdictive monitoring of text comprehension (i.e., the ability to judge the accuracy of responses previously given to a reading comprehension test) was investigated in both typically developing (TD) children and children with reading comprehension difficulties. Children from primary school (3rd to 5th grade) and secondary school (6th to 8th grade) participated in the study (N = 245). They were administered standardized tasks for reading comprehension, in which they had to read two texts and answer 12 multiple-choice questions after each text; subsequently, they had to provide postdictive judgments evaluating their performance: for each answer they had to select whether they judged it as correct, incorrect or whether they were uncertain. Two scores were calculated: Bias score, indicating the difference between metacognitive judgments of accuracy and actual performance; and Accurate estimation, indicating the sum of correct answers judged as “correct” and incorrect answers judged as “incorrect”. Results showed that primary school children were more overconfident than secondary school children and made fewer Accurate estimations especially for “correct” responses. Furthermore, the consideration of a group of children with reading comprehension difficulties showed that these failures are linked to worse metacognitive monitoring ability of comprehension performance in comparison not only to age-matched controls but also to the TD group of third-graders. Implications for learning and achievement are discussed.